Diagnostic Algorithm for Encephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Diagnostic algorithm for initial evaluation of encephalitis in children is proposed with a consensus statement from the International Encephalitis Consortium, a committee begun in 2010 to serve as a practical aid to clinicians evaluating patients with suspected encephalitis.